Interleukin-6: A cytokine to forget - Balschun, D. (2004)
It is known that proinflammatory cytokines such as interleukin-6 (IL-6) are expressed in the central nervous system (CNS) during disease conditions and affect several brain functions including memory and learning. In contrast to these effects observed during pathological conditions, here we describe a physiological function of IL-6 in the “healthy” brain in synaptic plasticity and memory consolidation. During long-term potentiation (LTP) in vitro and in freely moving rats, IL-6 gene expression in the hippocampus was substantially increased. This increase was long lasting, specific to potentiation, and was prevented by inhibition of N-methyl-Daspartate receptors with (±)-2-amino-5-phosphonopentanoic acid (AP-5). Blockade of endogenous IL-6 by application of a neutralizing anti-IL6 antibody 90 min after tetanus caused a remarkable prolongation of LTP. Consistently, blockade of endogenous IL-6, 90 min after hippocampus-dependent spatial alternation learning resulted in a significant improvement of long-term memory. In view of the suggested role of LTP in memory formation, these data implicate IL-6 in the mechanisms controlling the kinetics and amount of information storage.